IMPLEMENTASI ETIKA BISNIS ISLAM DALAM PENGELOLAAN USAHA KOPONTREN (Studi Kasus: Kopontren Qomaruddin Bungah Gresik) - Indriya Safitri; Kurniawan, Aries; Aulia Rahmi, Vembri; Ismanto, Hadi (Al-Maqashid: Journal of Economics and Islamic Business, 2023)
Judging from the continued increase in the number of students at the Qomaruddin Islamic Boarding School, it will always be accompanied by the increasing needs of the students that must be met, starting to increase the number of students will indirectly have an impact on the increase in several businesses. Kopontren business development is one way to improve the economy at the Qomaruddin Bungah Gresik Islamic boarding school. This research aims to determine the implementation of Islamic business ethics in the management of the Qomaruddin Kopontren business using qualitative methods with a descriptive approach starting from observation techniques after which data analysis is carried out from interviews and other sources. The results of this research indicate that the application of business ethics at Kopontren Qomaruddin generally works well in conventional or general business settings, whereas in the perspective of Islamic business ethics it goes well following the guidelines for Islamic business ethics but there is an interest system run by the Qomaruddin Kopontren which contains elements of usury which is forbidden in Islam. So that the application of Islamic business ethics has not been fully realized.